Improvements in water clarity and submersed aquatic vegetation cover after exclusion of invasive common carp from a large freshwater coastal wetland, Delta Marsh, Manitoba - Kowal, Paige D.; Badiou, Pascal; Emery, Robert B.; Goldsborough, L. Gordon; Wrubleski, Dale A.; Armstrong, Llwellyn M.; Page, Bryan (Frontiers in Environmental Science, 2022)
Once introduced to shallow aquatic ecosystems common carp (Cyprinus carpio; hereafter carp) often degrade habitat, negatively impacting the native organisms that rely on these systems. Detrimental effects often observed following the introduction of carp include a reduction in water clarity as bottom sediments become disturbed and resuspended and phytoplankton blooms become more severe and frequent. This results in a reduction of submersed aquatic vegetation (SAV), the effects of which are felt across multiple trophic levels. We sought to limit large carp (> 70 mm maximum body width) access to a culturally and biologically significant 18,500ha freshwater coastal wetland located in Manitoba, Canada to restore pre-carp conditions which were characterized by clear water and abundant SAV. In winter 2012–2013, exclusion structures were built to limit access by large carp to Delta Marsh during the spring and summer. A monitoring program (2009–2018) compared marsh conditions before and after carp exclusion. Water clarity improved following carp exclusion, largely driven by a reduction of inorganic suspended solids (ISS) rather than phytoplankton biomass, indicating that maintaining clear water conditions might be supplemented by reductions in nutrient export from agricultural areas adjacent to the marsh. The decrease in ISS and phytoplankton varied spatially, with the greatest change observed in the westernmost area of the marsh which is more sheltered compared to the large open bays characterizing eastern areas of the marsh. SAV doubled in percent cover through the six years of monitoring post-carp exclusion and SAV cover and species richness in the marsh was comparable to what was present in the early 1970s when there was also partial carp exclusion. Similar to water clarity, the increase in SAV cover was most significant in sheltered areas of the marsh. Our results suggest that excluding large carp can improve water clarity, SAV cover, and SAV species richness in large freshwater wetlands, benefiting waterfowl and other species.